Myopia and night lighting in children in Singapore - Saw, S. (2001)
AIM—To examine the role of night time lighting and myopia in children in Singapore METHODS—A cross sectional study was conducted on 1001 children in two Singapore schools. Cycloplegic refraction and A-scan biometry measurements were made in both eyes. A detailed questionnaire was completed by the parents to obtain information on night time lighting, near work activity, educational and demographic factors. RESULTS—There was no difference in myopia prevalence rates in children exposed to night time light (33.1%) compared with children who slept in the dark (31.4%) before age 2. In addition, vitreous chamber depth was not related to night light (p=0.58) before age 2. These results remained even after controlling for near work. CONCLUSION—Myopia is not associated with night light in Asian populations.